Economics of chhari and marketable-size carps in Bara, Nepal - Adhikari, Prabin; Jha, Dilip Kumar; Poudel, Mousami; Gurung, Suraj; Acharya, Mahesh Chandra (Journal of Agriculture and Natural Resources, 2019)
A study was conducted to analyze the economics of production of chhari and marketable-size carps in Bara, Nepal. All total 90 farmers; 45 chhari producing and 45 marketable-size carps producing farmers were selected randomly and surveyed through pre-tested semi-structured interview based schedule on the month of March, 2019. Data was entered and analyzed using STATA 12.1 and SPSS 25. Findings of the study revealed that the total cost of fish production per hectare of pond area was 971927 NRs/year. Chhari production was profitable in the study area as compared to marketable-size carps with a Benefit Cost Ratio of 1.97 and 1.67 respectively. Production function analysis including six explanatory variables, showed significant effect of feed, labour (p<0.01), maintenance, fuel and electricity (p<0.05) and lime, fertilizer and medicine costs (p<0.1) but seed cost was insignificant. The return to scale was found to be 0.906 and at II stage of Production. According to estimated allocative efficiency indices, it is suggested to reduce seed; and lime, fertilizer cum medicine cost by 159% and 72% respectively, and increase the maintenance; feed; fuel cum electricity; and labour cost by about 95%, 33%, 95%, and 50% respectively for chhari producers. Similarly for marketable-size carp producers, it is suggested to decrease fuel and electricity cost by 176% and increase maintenance; seed; feed; lime, fertilizer and medicine; and labour cost by 95%, 86%, 13%, 29%, and 30% respectively. Thus, fishery enterprise is in the stage of higher potentiality to increase the production in the study area.